Different Roles of Mast Cells in Obesity and Diabetes: Lessons from Experimental Animals and Humans - Shi, Michael A.; Shi, Guo-Ping (Frontiers in Immunology, 2012)
Mast cells (MCs) play an important role in allergic hyperresponsiveness and in defending microorganism infections. Recent studies of experimental animals and humans have suggested that MCs participate in obesity and diabetes. MC distribution and activities in adipose tissues may vary, depending on the locations of different adipose tissues. In addition to releasing inflammatory mediators to affect adipose tissue extracellular matrix remodelling and to promote inflammatory cell recruitment and proliferation, MCs directly and indirectly interact and activate adipose tissue cells, including adipocytes and recruited inflammatory cells. Plasma MC protease levels are significantly higher in obese patients than in lean subjects. Experimental obese animals lose body weight after MC inactivation. MC functions in diabetes are even more complicated, and depend on the type of diabetes and on different diabetic complications. Both plasma MC proteases and MC activation essential immunoglobulin E levels are significant risk factors for human pre-diabetes and diabetes mellitus. MC stabilization prevents diet-induced diabetes and improves pre-established diabetes in experimental animals. MC depletion or inactivation can improve diet-induced type 2 diabetes and some forms of type 1 diabetes, but also can worsen other forms of type 1 diabetes, at least in experimental animals. Observations from animal and human studies have suggested beneficial effects of treating diabetic patients with MC stabilizers. Some diabetic patients may benefit from enhancing MC survival and proliferation — hypotheses that merit detailed basic researches and clinical studies.